Vaginal Yolk Sac Tumor in an Infant. Issue 5 (July 2015) - Bhatt, Mihir D.; Braga, Luis H.; Stein, Nina; Terry, Jefferson; Portwine, Carol
<x xml:space="preserve">Abstract</x> Vaginal yolk sac tumor is a rare malignant germ-cell tumor occurring most commonly in young girls. The treatment has evolved over the last 3 decades from radical surgery to conservative surgery with chemotherapy to chemotherapy alone. Here we present a case of a 6-month-old girl successfully treated with upfront surgery followed by chemotherapy. We include a literature review of studies on vaginal yolk sac tumor published in the last 30 years. We discuss the role of upfront surgery where possible followed by chemotherapy as a safe alternative to chemotherapy alone for the treatment of this rare malignancy.